Faktor-Faktor yang Mempengaruhi Self-care Behavior pada Klien dengan Hipertensi di Komunitas - Wimar Anugrah Romadhon; Bernadetta Germia Aridamayanti; Anggi Hanafiah Syanif; Gevi Melliya Sari (FORIKES, 2020)
Background: self-care behavior is an important thing that needs to be considered by clients with hypertension which consists of several components, namely the use of drugs, low-salt diet, physical activity, smoking, weight management and alcohol consumption. Purpose: to show the factors that influence self-care behavior in clients with hypertension. Method: the database used to identify suitable articles obtained from Scopus, ProQuest and Google Scholar, limited to the last 5 years of publication from 2014 to 2019, English, and fulltext articles. The literature review used the keyword